“Construcción de circuitos lúdicos para el fortalecimiento de las áreas psicomotrices”. - Aguilar Vergara, Anahis Auxiliadora (2024)
This research project focuses on children's psychomotor skills with the aim of understanding the importance of psychomotor domains for their holistic development. An innovative methodology based on playful work is proposed to maximize their abilities and skills. It is crucial to emphasize that children's psychomotor skills have been excluded from current educational methods, and even more so in rural areas. This has led to difficulties in the learning and holistic development of infants. In response to the results of the study, it is proposed to build play circles for each psychomotor area to strengthen it in children aged 4 to 5 years and to promote the weak areas. A qualitative approach based on field research and descriptive, inductive, historical and bibliographic methods was chosen to carry out this study, as it is based on the reality and experiences of the children in the educational process. In order to collect information, observation and interview techniques were used, using instruments such as the checklist and the question guide. The analysis of the results revealed that the lack of resources in educational institutions has limited the integral development of children, generating a lack of motivation to learn.